x-8=6x-13

Simple and best practice solution for x-8=6x-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-8=6x-13 equation:


Simplifying
x + -8 = 6x + -13

Reorder the terms:
-8 + x = 6x + -13

Reorder the terms:
-8 + x = -13 + 6x

Solving
-8 + x = -13 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-8 + x + -6x = -13 + 6x + -6x

Combine like terms: x + -6x = -5x
-8 + -5x = -13 + 6x + -6x

Combine like terms: 6x + -6x = 0
-8 + -5x = -13 + 0
-8 + -5x = -13

Add '8' to each side of the equation.
-8 + 8 + -5x = -13 + 8

Combine like terms: -8 + 8 = 0
0 + -5x = -13 + 8
-5x = -13 + 8

Combine like terms: -13 + 8 = -5
-5x = -5

Divide each side by '-5'.
x = 1

Simplifying
x = 1

See similar equations:

| B^5=368 | | 2x+3=51-2x | | 2x+18-4x+12=-6 | | -2=2+(.25)v | | 4(3+c)=3(c-5) | | (x-3).6(x+1)=65 | | 9+(-2)=4+t | | 7x+1=31+4x | | 0.60x+.05(4-x)=.10(-20) | | 3(2x+6)=-6 | | 2m-9-8m=27 | | 6-2(4-8x)=2(3x-5) | | 2.5=d-(20) | | x-(3x+7)=11 | | x-6=-12+2x | | 2.5=d-(.20) | | -9+5x=-5x+1 | | 6.8x-15.3+4.2x=6.4+12x | | b=85+(23)w | | x+8=5x+52 | | 7x+19+-2x=55 | | -3x-5=-47+4x | | 5m-2(4m-1)=-14 | | 10=3x-5x+6 | | x-5-8x=16 | | -14x-4(2x-5)=9 | | -x+6+2x=13 | | 18=8-6b | | (30+5x)+(10x+15)=180 | | (x+6)(3x+8)=0 | | -1-5x+3x=1 | | y-5-2=10 |

Equations solver categories